2007
DOI: 10.1111/j.1440-1843.2007.01167.x
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary complications of HIV infection

Abstract: The AIDS epidemic has had a devastating global impact in the last two decades; although prevalence rates are low in Asia and the Pacific, their enormous population is associated with an estimated 1 million people infected with HIV in 2006 alone. Survival from what had been a uniformly fatal illness has improved markedly with combination antiretroviral therapy and restoration of the immune system, but these treatments are expensive and difficult to distribute to the millions who need them around the world. In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 40 publications
0
17
1
2
Order By: Relevance
“…In fact, almost 70% of people infected with HIV suffer at least one pulmonary complication during the course of the infection (2). Although in early HIV infection the agents that cause pneumonia are similar to those found in the general population, when the number of CD4 ϩ T cells decreases, opportunistic pneumonias are associated with high morbidity and mortality (3)(4)(5). Tuberculosis and Pneumocystis jirovecii pneumonia (PCP; the abbreviation PCP reflects the previous nomenclature for the Pneumocystis species causing opportunistic pneumonia in humans, P. carinii; P. jirovecii is now recognized as the species that infects humans) are the most commonly reported AIDS-defining illnesses (6).…”
mentioning
confidence: 99%
“…In fact, almost 70% of people infected with HIV suffer at least one pulmonary complication during the course of the infection (2). Although in early HIV infection the agents that cause pneumonia are similar to those found in the general population, when the number of CD4 ϩ T cells decreases, opportunistic pneumonias are associated with high morbidity and mortality (3)(4)(5). Tuberculosis and Pneumocystis jirovecii pneumonia (PCP; the abbreviation PCP reflects the previous nomenclature for the Pneumocystis species causing opportunistic pneumonia in humans, P. carinii; P. jirovecii is now recognized as the species that infects humans) are the most commonly reported AIDS-defining illnesses (6).…”
mentioning
confidence: 99%
“…Pre-ART (antiretroviral therapy) era studies, including autopsy-based, reported that CMV disease was recognized in endstage AIDS patients before death in up to 40% and at autopsy in up to 90% at that time [30]. Since the introduction of ART, CMV incidence and the related mortality among AIDS patients have declined.…”
Section: Introductionmentioning
confidence: 99%
“…In advanced stages of HIV course, cavitary TB is uncommon and lower-lobe infi ltrates or miliary dissemination as well as extrapulmonary TB usually occurs [6,15]. If extrapulmonary TB develops in immunocompetent individuals, no active pulmonary lesions are usually found at that time; however, in HIV/AIDS patients disseminated TB is characterized by simultaneous involvement of the lungs and other organs [16,30].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations